Coat-colour-related genotypes, phenotyping and biometric assessment of three ecotypes of pigs in Cameroon - A. I. Nono Ekane; F. Ngoula; B. A. Hako Touko (Archives Animal Breeding)
A study was conducted from June 2022 to December 2023 in three agroecological zones in Cameroon to describe the local pigs and to develop a standard method for reporting their phenotypic-diversity information. A systematic sample of 152 adult pigs was considered and described in terms of coat colour major genes and body measurements. The results show that local pigs are heterogeneous in colour and are predominantly white (34.2 %). The melanocortin 1 receptor gene (MC1R) was the most significant gene for primary coat colour, with five alleles, including E+ (wild type), E (dominant black), Ed (black with white belt), Ep (white with black spots) and e (recessive red). The Ep allele was the most predominant at 75 % allele frequency. The agouti signalling protein (ASIP) gene was the only secondary coat colour determiner observed, with its recessive non-agouti allele (a) present (100 %). The coat colour modifier is the tyrosine-kinase protein gene (KIT), with six alleles, including I (colour inhibition), Id (green), Ip (white and black spots), Ib (white belt), im (dirty white) and i (non-kit), with the predominant allele being Ip (39.5 %). The agroecological zone influenced body measurements, including head length, between-ear distance, snout size and ischium width (P < 0.05). Furthermore, the highest live weight of 82.47 ± 23.86 kg was obtained in the monomodal-rainfall forest (MRF) zone. The biometrical structure shows that the local Cameroon pigs can be organised into three subgroups. This study provides the broader audience with valuable insights into the phenotypic diversity of the local Cameroon pigs and a standardised description and reporting protocol.